2014
DOI: 10.1007/s11999-014-3640-8
|View full text |Cite
|
Sign up to set email alerts
|

Ilizarov Fixator Combined With an Intramedullary Nail for Tibial Nonunions With Bone Loss: Is It Effective?

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…This is decreased compared with other studies of Ilizarov tibial reconstruction, which have rates that range between 2.1 and 2.6 per patient [2,8,15,37]. There was no difference in the number or severity of adverse event in both groups.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This is decreased compared with other studies of Ilizarov tibial reconstruction, which have rates that range between 2.1 and 2.6 per patient [2,8,15,37]. There was no difference in the number or severity of adverse event in both groups.…”
Section: Discussionmentioning
confidence: 52%
“…Association for the Study and Application of Methods of Ilizarov bone results were excellent in all five patients. Four patients reported excellent Association for the Study and Application of Methods of Ilizarov function results, whereas one patient was reported as good [15]. In a study of 28 patients with open tibial fractures, Atef and El-Tantawy [2] reported 16 excellent results, nine good, two fair, and one poor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…His treatment of choice was intramedullary nailing combined with bone resection, compression and distraction of the Ilizarov apparatus and autografting at the docking site. The grafts were harvested from the iliac crest [30]. In our case, the nail was already placed inside the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Acute shortening of tibial defects of £4 cm displayed no arterial changes as monitored by intraoperative Doppler ultrasound and hallux pulse oximetry 69 . Five patients with tibial nonunions and bone loss were treated successfully with acute shortening and bone-grafting and gradual lengthening over a nail via a corticotomy at a different portion of the affected tibia 70 . Other reported methods for managing posttraumatic skeletal defects or voids include the induced membrane technique 71 , hybrid grafting using demineralized bone matrix and tricalcium phosphate 72 , nonvascularized fibular strut bone grafts 73 , combined Papineau debridement and Ilizarov bone transport with postoperative negative-pressure wound closure 74 , epidermatofascial osteoplasty 75 , and use of megaprostheses 76 .…”
Section: Bone Defectsmentioning
confidence: 99%